2004
DOI: 10.1116/1.1689303
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent characteristics of bulk GaN Schottky rectifiers on free-standing GaN substrates

Abstract: The performance of Schottky rectifiers fabricated with dielectric overlap edge termination on epitaxial layers grown on a free-standing GaN template is reported. The power figure-of-merit (VB)2/RON where VB is the reverse breakdown voltage and RON is the on-state resistance was 11.5 MW cm−2. The forward turn-on voltage was ∼3.5 V at 25 °C, with an on-state resistance of ∼5×10−3 Ω cm2. The reverse recovery time was ⩽50 ns in switching from forward bias to reverse bias. The reverse breakdown showed a temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Impurity trace analysis of this 14 mm thick film indicates that low background impurity levels were achieved, which is a basic requirement for high breakdown blocking layers in fast switches. This preliminary result is quite encouraging, but numerical calculation indicates that to achieve a 10 kV breakdown voltage, films with 1 Â 10 15 /cm 3 free carrier concentration must have thickness exceeding 50 mm [3]. These relatively large required film thicknesses make difficult the use of deposition techniques such as MOCVD, which has growth rates typically on the order of 2 mm/h.…”
Section: Introductionmentioning
confidence: 70%
“…Impurity trace analysis of this 14 mm thick film indicates that low background impurity levels were achieved, which is a basic requirement for high breakdown blocking layers in fast switches. This preliminary result is quite encouraging, but numerical calculation indicates that to achieve a 10 kV breakdown voltage, films with 1 Â 10 15 /cm 3 free carrier concentration must have thickness exceeding 50 mm [3]. These relatively large required film thicknesses make difficult the use of deposition techniques such as MOCVD, which has growth rates typically on the order of 2 mm/h.…”
Section: Introductionmentioning
confidence: 70%
“…defect densities must be reduced. A theoretical calculation for the breakdown voltage of a GaN punch-through diode indicates that over 1000 V can be achieved with a 5 mm thick blocking layer and a donor concentration of 5 Â 10 15 cm À 3 [3]. Experimental results reveal much lower breakdown voltages indicating that processing and growth induced defects are the major contributions for premature breakdown [3].…”
Section: Introductionmentioning
confidence: 95%
“…A theoretical calculation for the breakdown voltage of a GaN punch-through diode indicates that over 1000 V can be achieved with a 5 mm thick blocking layer and a donor concentration of 5 Â 10 15 cm À 3 [3]. Experimental results reveal much lower breakdown voltages indicating that processing and growth induced defects are the major contributions for premature breakdown [3]. Zhang et al [5] demonstrated that vertical devices fabricated with several microns thick homoepitaxial films reach a figure-of-merit (FOM) as high as 48 MW/cm 2 , exceeding the 15.5 MW/cm 2 value achieved with optimized planar devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Introduction Freestading GaN substrates have been used to improve performances of light-emitting devices and high-power devices [1][2][3]. GaN substrates have been fabricated from thick GaN layers grown by hydride vapor phase epitaxy (HVPE) on c-plane sapphire using buffer layers which are followed by the separation of the thick GaN layers from the c-plane sapphire substrates.…”
mentioning
confidence: 99%